Diabetes mellitus is associated with an increased incidence of aortic valve stenosis. (October 2021) - Roderburg, Christoph; Loosen, Sven H; Luedde, Tom; Kostev, Karel; Luedde, Mark
Background: The prognosis of patients with diabetes mellitus (DM) is particularly determined by vascular comorbidities. A recent theory implies that DM could also promote aortic valve stenosis (AS). The present study investigates this association in a large collective of outpatients. Methods: This retrospective cohort study compared the incidence of AS in patients with an initial diagnosis of type 2 DM and a matched non-DM cohort in 809 general and diabetologist practices in Germany between January 2005 and December 2018. Cox regression models were performed to study the association between type 2 DM and AS incidence. Results: A total of 78, 805 patients with type 2 DM and 78, 805 patients without diabetes were analysed. Diabetes patients were more frequently diagnosed with obesity (52% vs 21%). Four percent of patients with and three percent of without diabetes were diagnosed with AS ( p < 0.001). Diabetes was significantly associated with an increased incidence of AS (HR: 1.36, p < 0.001). This association was higher in men (HR: 1.41) versus women (HR: 1.30). The strongest association was observed in young patients (18–50 years, HR: 2.35, p < 0.001). Conclusion: In our study, diabetes patients had a higher incidence of aortic stenosis during their disease course.